Changing Concept in the Management of Ectopic Pregnancy - A Case Report (Journal of Shaheed Suhrawardy Medical College, 2018)
Ectopic pregnancy remains the great puzzle of gynaecology, no other pelvic condition gives rise to more diagnostic error like this condition. In the last 20 years, the management of ectopic pregnancy has evolved from a radical operative procedure to a more conservative approach. This case report describes a woman who experienced tubal ectopic pregnancy twice, with two different methods of management. In the first time she had left sided ruptured tubal ectopic pregnancy which was managed by laparoscopic left sided salphingectomy. In the next time, her right tube was involved with ectopic pregnancy. This time, she was decided to be managed by conservative medical treatment. The patient was treated with a single dose of injection methotrexate 50 mg intramuscularly. She was monitored closely at 4-5 days interval. At the 19th day, she was found to have complete resolution of the ectopic sac.J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 73-75